Open Access and Scholarly Communication — A Selection of Key Web Sites - Hanna Kwasik; Pauline O. Fulda (Issues in Science and Technology Librarianship)
Presents a list of Web sites that are related to open access and scholarly communication. Ifla.org/index.htm; Arl.or/sparc/; Informationaccess.org.